(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the place of books and libraries in medieval Andalusia (711–1492) and shows how, in Cordoban society, the possession of books and the building of personal libraries became an important marker of a person’s social status. Drawing on the patronage of the Umayyad rulers of al-Andalus, especially al-Hakam I, Abd al-Rahman II, and al-Hakam II, it describes the founding of the great library of Cordoba, the work of the book-collectors (warraqun) and copyists (nussakh), and the broad culture of book-collecting that distinguished the people of al-Andalus.